2018
DOI: 10.1016/j.celrep.2018.09.079
|View full text |Cite
|
Sign up to set email alerts
|

The Cdkn1aSUPER Mouse as a Tool to Study p53-Mediated Tumor Suppression

Abstract: Highlights d An extra p21 copy enforces cell-cycle arrest and protects from DNA-damaging agents d Increased p21 gene expression delays epithelial regeneration and blocks apoptosis d Mice harboring a third Cdkn1a allele display cancer protection d The tumor suppressors p21 and p53 cooperate in mediating cancer resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…p21 has been linked with DKD previously, but the regulation of p21 and its role in hyperglycemic memory are not known (40)(41)(42)(43). The role of p21 in tubular senescence in DKD is in agreement with previous observations: (i) the level and duration of p21 induction determine the onset of cellular growth arrest, (ii) p21 expression is sufficient to induce senescence, (iii) p21 expression restricted to tubular cells is sufficient to induce renal fibrosis following acute kidney injury (44)(45)(46), and (iv) p21 induces endoreduplication (47), which may impair renal tubular cell recovery following acute kidney injury (48,49). These and the current data support a model in which prolonged and sustained p21 expression causes tubular senescence and compromises tubular repair capacity in DKD patients (50), even after glycemic control has improved.…”
Section: Discussionsupporting
confidence: 91%
“…p21 has been linked with DKD previously, but the regulation of p21 and its role in hyperglycemic memory are not known (40)(41)(42)(43). The role of p21 in tubular senescence in DKD is in agreement with previous observations: (i) the level and duration of p21 induction determine the onset of cellular growth arrest, (ii) p21 expression is sufficient to induce senescence, (iii) p21 expression restricted to tubular cells is sufficient to induce renal fibrosis following acute kidney injury (44)(45)(46), and (iv) p21 induces endoreduplication (47), which may impair renal tubular cell recovery following acute kidney injury (48,49). These and the current data support a model in which prolonged and sustained p21 expression causes tubular senescence and compromises tubular repair capacity in DKD patients (50), even after glycemic control has improved.…”
Section: Discussionsupporting
confidence: 91%
“…The GO analysis results indicated that the altered m 6 A methylated transcripts were mainly associated with intracellular, binding, and cell part, which were closely related to the adverse effect of ROS, implying that the m 6 A modification might be essential for the oxidative stress response in AKI. In addition, further analysis demonstrated that the parent genes of the top three altered methylated mRNAs (Fosl1, Krt20, and Cdkn1a) participated in regulating apoptotic pathways (Torgovnick et al, 2018;. A study conducted by Shen J et al also found that genes with elevated methylation of m 6 A sites were significantly enriched in the cell death processes, such as apoptotic processes (Shen J. et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, 4-1BB is an established marker of exhausted CD8 + T cells (72,73). Lastly, the p53 target gene Cdkn1a (p21) is a potent CDK inhibitor involved in p53-mediated cell-cycle arrest (74). Reduced expression of Cdkn1a in CD4 + T cells following PD-1 blockade thus might be in line with restored proliferation potential.…”
Section: Human Abc-dlbcl and Murine Mbc-derived Lymphomas Display An Actionable Pd-l1 Expressionmentioning
confidence: 99%